1991
DOI: 10.1172/jci115463
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli hemolysin is a potent inductor of phosphoinositide hydrolysis and related metabolic responses in human neutrophils.

Abstract: Escherichia coli hemolysin (Hly) is a proteinaceous pore-forming exotoxin that probably represents a significant virulence factor in E. coli infections. We investigated its influence on human polymorphonuclear neutrophils (PMN), previously identified as highly susceptible targets. Hly provoked rapid secretion of elastase and myeloperoxidase, generation of superoxide, and synthesis of platelet-activating factor (PAF) and lyso-PAF. Concomitantly, marked phosphatidylinositol (Ptdlns) hydrolysis with sequential ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
1
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 61 publications
4
46
1
1
Order By: Relevance
“…The THP-1 monocytes also express P2Y 2 receptors, which is likely responsible for the HlyA-induced IP 3 degradation observed in leukocytes (79). Here, we show that stimulation of P2Y receptors by UTP significantly potentiated cell lysis in THP-1 monocytes.…”
Section: Discussionsupporting
confidence: 51%
“…The THP-1 monocytes also express P2Y 2 receptors, which is likely responsible for the HlyA-induced IP 3 degradation observed in leukocytes (79). Here, we show that stimulation of P2Y receptors by UTP significantly potentiated cell lysis in THP-1 monocytes.…”
Section: Discussionsupporting
confidence: 51%
“…Bauldry [ 191 also reported no cytochrome-c-specific reduction by atoxin in the presence of 100 pM NADPH. As already cited above, Grimminger [20] showed that a-toxin induced in human neutrophils no cellular responses. All together, these results indicate this is a reproducible method for eosinophil and neutrophil peimeabilization, leaving the cells in a permeable, well functioning and intact state.…”
Section: Discussionmentioning
confidence: 71%
“…Production of Ins(1,4,5)P 3 has also been shown to be triggered by two other pore-forming proteins. Grimminger et al (33,35) have shown that Escherichia coli hemolysin (HlyA) leads to phosphoinositide hydrolysis and production of diacylglycerol but the mechanism by which HlyA triggered a G-proteindependent pathway was not further analyzed (33,35). The C5b-9 membrane attack complex was also shown to trigger mobilization of calcium from intracellular stores secondary to activation of phospholipase C and production of Ins(1,4,5)P 3 (36,37).…”
Section: Discussionmentioning
confidence: 99%